1995
DOI: 10.1002/ijc.2910610205
|View full text |Cite
|
Sign up to set email alerts
|

Expression of fgf and fgf receptor genes in human breast cancer

Abstract: The family of FGF growth factors is involved in several biological processes and might play an important role in tumorigenesis. We have studied the respective expression of 8 of the 9 characterized FGF genes, and of the 4 known FGF receptor genes, in a panel of 10 tumor-cell lines and 103 breast-tumor samples, using RT-PCR and Northern-blot analyses. FGF1 and FGF2 were expressed in almost all samples, while expression of FGF5, FGF6, FGF7, and FGF9 was more restricted. FGFR1, FGFR2 and FGFR4 were expressed at h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
148
2
3

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(163 citation statements)
references
References 17 publications
10
148
2
3
Order By: Relevance
“…It has previously been shown that the predominant form of FGFR-1 mRNA transcribed is the 5-form with the a-form present as a minority species (Luqmani et al, 1995;Penault-Llorca et al, 1995). Our results show that this is also the case for the receptor proteins.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…It has previously been shown that the predominant form of FGFR-1 mRNA transcribed is the 5-form with the a-form present as a minority species (Luqmani et al, 1995;Penault-Llorca et al, 1995). Our results show that this is also the case for the receptor proteins.…”
Section: Discussionsupporting
confidence: 78%
“…Our results show that the FGFR-1 mRNA previously described in breast cell lines and human breast cancers (Lehtola et al, 1992;Luqmani et al, 1992;Luqmani et al, 1995;Penault-Llorca et al, 1995) does get translated into protein. It has previously been shown that the predominant form of FGFR-1 mRNA transcribed is the 5-form with the a-form present as a minority species (Luqmani et al, 1995;Penault-Llorca et al, 1995).…”
Section: Discussionsupporting
confidence: 66%
“…Indeed, the FGFR-1, FGFR-2 andFGFR-3 genes are amplified in 12.7%, 11.5% and 10% of breast cancers, respectively; they are also expressed at high levels in, respectively, 22%, 4% and 32% of the breast tumor samples [14,15]. Messenger RNAs for fgf-1, fgf-2 are present in all samples of breast cancer; whereas mRNA for fgf-5, fgf-6, fgf-7, fgf-8 and fgf-9 are detectable in various percentages of the tumor samples [14,15]. The production of FGF-1 and FGF-2 is down-regulated in the tumoral cells in comparison with normal tissue or begnin tumors [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…MCF7 breast cancer cells were chosen, since their low tumorigenicity and the presence of estrogen and progesterone receptors [23] are interesting properties to study the progression of breast cancer cells in particular from hormonedependence to hormone-independence [24,25]. The messenger RNA for the four FGF receptor genes are detected in MCF7 cells [14,26]. Thus, it was demonstrated that MCF7 cells that overexpress FGF-1 become tumorigenic and metastatic in mice not supplemented with estrogen [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…It is produced by stromal fibroblasts and acts via the KGF receptor (FGFR2-IIIb) on epithelial cells . Other studies show no expression of FGF3 and FGF4 in human breast cancers but expression of all other FGFs in at least a small proportion of breast cancers (Penault-Llorca et al, 1995). All four of the FGFRs are expressed to some degree in breast cell lines (McLeskey et al, 1994;Johnston et al, 1995).…”
mentioning
confidence: 97%